Mawenzhangia thamnobryoides (Bryophyta, Lembophyllaceae), a new moss genus and species from the Shangri-la region of Yunnan Province, China - Enroth, Johannes; Shevock, James R.; Ignatov, Michael S. (Phytotaxa, 2018)
Mawenzhangia thamnobryoides gen. et sp. nov. (Bryophyta, Lembophyllaceae) is described based on collections from Yunnan, China. It is known from the Niru River watershed and grows on boulders just above the high water zone but can also be seasonally inundated. According to ITS sequences it is closely related to Nogopterium gracile (Pterogonium g.), but can be distinguished by the loosely patent and elliptic vs. imbricate and ovate leaves; much longer, single costa; thinner-walled and less strongly prorate laminal cells; and much smaller group of alar cells. Mawenzhangia thamnobryoides is illustrated in line drawings and an identification key to Chinese genera of the Lembophyllaceae is provided.